Web-Based Measuring Instrument Calibration Scheduling Information System: Case Study of One of the Textile Companies in Bandung City - Amalia, Fika; Riswaya, Asep Ririh (Electronic, Business, Management and Technology Journal, 2023)
The production method has prioritized guaranteeing excellent manufacturing quality in response to the increasing competitiveness in the clothing industry. Utilizing a fabric roll meter measuring instrument dramatically enhances the overall quality of the product by guaranteeing precise measurements. Roll meter fabric measuring equipment in the garment industry evaluates product accuracy based on customer specifications, ensuring exceptional quality. Effective regulation is essential for the management and upkeep of cloth roll meter measuring instruments. Therefore, it is necessary to develop a system that can evaluate the level of urgency for calibrating various equipment and identify those that need recalibration despite having already been calibrated. This project created a web-based system for scheduling the calibration of fabric roll meters. The system was designed using the PHP programming language and MySQL for database management. Use cases delineate how the user interacts with the system, whereas an activity diagram represents the sequence of user activities. Furthermore, a sequence diagram illustrates the user's participation in chronological order. The information system implements maintenance schedules, oversees the calibration of fabric roll meter measuring instruments, stores calibration certificates, and effectively handles calibration data to guarantee precision and efficiency.